(untitled) (Archive of Conferences, 2020)
One of the main directions of reforming lifelong education in the Republic of Uzbekistan is training, retraining and advanced training of personnel in accordance with the prospects of social and economic development of the country, the needs of society, modern achievements of science, culture, technology and technology. The changes taking place in the Republic bring their own adjustments to the working conditions of the teacher.